E-TITUDE: INNOVATION OF ISLAMIC MORALS LEARNING APPLICATIONS FOR YOUTH BASED ON VIRTUAL REALITY TO FACE QUALITY EDUCATION IN 2030 - Rifai, Iif Ahmad; Safrani, Irma Della Pupita; Insani, Haifa Putri (Universitas Islam Indonesia, 2021)
Background: Indonesia is a country with the highest number of young and productive ages. The negative phenomena that surface and often become a spectacle in everyday life whose sources are through the print and electronic media of teenagers in Indonesia, causing this immoral case to occur in adolescents not only related to social norms, but also religious norms. This immoral behavior shows the erosion of morals based on Islamic values . Apart from that, the role of education is the main focus in educating to foster the religiosity of teenagers based on the beliefs and understanding of teenagers about God, the Holy Scriptures, and religious teachings that need to be actualized in daily behavior to carry out teachings and obligations related to religion and be ready accept all the consequences. In this regard, efforts to improve the quality of education require special attention to the cultivation of morals based on Islamic teachings in order to encourage the achievement of sustainable development goals and objectives in meeting the Sustainable Development Goals (SDGs). Based on the 4th achievement which has a target to ensure quality education, also supports lifelong learning opportunities for all in welcoming quality education in 2030. Method: This scientific paper uses the literature study method as the type of writing . Results: the application of E-TITUDE learning based on virtual reality make a real or imaginary environment is simulated and users can experience direct learning in Islamic moral learning for adolescents. Innovation The E-TITUDE application features a scoreboard, game play, and user interface designed to instill an understanding of the Islamic religion through challenges given according to daily applications. Conclusion: Therefore paper is a prototype of the E-TITUDE application is expected to be effective in implementing Islamic moral learning to meet quality education in 2030. Keywords: E-TITUDE Application, Youth, Islamic Morals, Sustainable Development Goals